Testing of composite slab-beam systems at elevated temperatures - Nguyen, Trung T. (2013)
This paper presents the results of experimental investigations on structural behaviour of composite slab-beam systems in simulated fire condition. Two 1/4 scale composite slab-beam systems, 3.15m by 3.15m in plan, were tested in fire. One of the two slabs had no interior beams, while the other had two unprotected interior steel beams. The tests were to examine the effects of protected deformed edge beams and unprotected interior beams on the behaviour of the floor assembles in fire. The results show that the continuity of reinforcement over supporting beams and the presence of interior beams can reduce deflection and greatly enhance the load-bearing capacity of the slab-beam systems. However, the presence of edge beams may lead to some failure modes which are different to those of isolated slabs.